The Effect of Combining the Competency Based Approach and the Multiple Intelligences Theory on the Development of EFL Students’ Speaking Skill - BOULMAIZ, Djallel (Journal of Human Sciences, 2019)
This paper investigates the extent to which change of teaching style affects students’ achievements, more specifically their development of the speaking skill within a specific academic subject-matter course. The researcher seeks to investigate whether learners’ performance on a specific topical knowledge speaking test will be enhanced if we implement an instructional design that incorporates the principles of the Competency-Based Approach and the Multiple Intelligences Theory. In order to achieve the research objective, a quasi-experiment was implemented at the level of the English department- Larbi Ben M’hidi University. The study was conducted on three intact first-year groups and it went over three phases: pretesting, treatment, and post-testing. The research findings revealed that combining the Competency-Based Approach and the Multiple Intelligences Theory yields better results in students’ development of the speaking skill.